2019
DOI: 10.4067/s0718-58392019000300405
|View full text |Cite
|
Sign up to set email alerts
|

Critical period of weed interference on total polyphenol content in quinoa

Abstract: There is limited information about the critical period of weed interference (CPWI) in quinoa (Chenopodium quinoa Willd.) and the effect produced by the weed-crop interaction in secondary metabolite accumulation. The objective of the present study was to determine the CPWI and its effect on total polyphenol content in quinoa. The experiments were conducted during two consecutive seasons using a randomized complete block design with 16 treatments consisting of 8 weed growth periods and 8 weed-free growth periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This variable was related directly to plant yield, which was higher in this treatment (data not shown). This can be due to the fact that when there is no competition with weeds or applied herbicides, photoassimilates are used in the growth and storage processes and form the optimal number of grains they can fill (Merino et al, 2019). There is also a direct influence of factors such as irradiance levels, water potential, nutrients, and duration of the formation of potential harvest organs on the number of these organs.…”
Section: Agronomic Variables and Yield Componentsmentioning
confidence: 99%
“…This variable was related directly to plant yield, which was higher in this treatment (data not shown). This can be due to the fact that when there is no competition with weeds or applied herbicides, photoassimilates are used in the growth and storage processes and form the optimal number of grains they can fill (Merino et al, 2019). There is also a direct influence of factors such as irradiance levels, water potential, nutrients, and duration of the formation of potential harvest organs on the number of these organs.…”
Section: Agronomic Variables and Yield Componentsmentioning
confidence: 99%
“…Studies have already reported that the lack of weed control may reduce the crop yield close to 100% 8–10 . Some crops have shown greater capacity to endure weed interference, but high losses were observed for soybean (70%), 11 corn (70%), 12 sesame (20%), 13 and cotton (18%) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies have already reported that the lack of weed control may reduce the crop yield close to 100%. [8][9][10] Some crops have shown greater capacity to endure weed interference, but high losses were observed for soybean (70%), 11 corn (70%), 12 sesame (20%), 13 and cotton (18%). 14 Even generating costs for producers, weed control can be economically viable if implemented at the necessary time to minimize interference.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known as the critical period of weed control [23] and defined as the duration of the crop life cycle in which it must be kept weed-free to prevent yield loss from weed interference. This period has been determined for many crop species, including wheat and found different between crops [24][25][26][27][28][29]. In competition of wheat (Triticum spp.)…”
Section: Introductionmentioning
confidence: 99%